Bahasa Inggris INTEGRATING THE 7 GREAT HABITS OF INDONESIAN CHILDREN INTO ISLAMIC CHARACTER EDUCATION: SUPPORTING SDG 4 (QUALITY EDUCATION): - - Muhajang, Tatang; Basari, Muhammad Hasan; Aflaha, Akhmad; Handayani, Fitri; Fatwanti, Devi; Fakhruzaman, Daden (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
In the era of digital transformation, the younger generation faces increasing moral challenges and value disorientation. Therefore, strengthening character education through sustainable and spiritually grounded habits is essential. This study aims to analyze the internalization of the 7 Great Habits of Indonesian Children from an Islamic educational perspective and examine their contribution to achieving Sustainable Development Goal 4 (Quality Education). This research employs a qualitative approach using a systematic literature review. Data were collected from scientific publications related to Islamic character education and sustainable education, then analyzed through reduction, categorization, and thematic synthesis. The findings indicate that the seven habits are strongly grounded in Islamic educational concepts such as tarbiyah, ta'dib, and tazkiyah al-nafs, reflecting values of monotheism, balance, discipline, and social responsibility. These values contribute to the formation of students’ spiritual, social, and ecological character, which aligns with the principles of inclusive and sustainable education promoted by SDG 4. This study contributes theoretically by proposing a conceptual framework for integrating Islamic character education and national habit-based programs into sustainable education. Practically, it highlights the importance of collaboration among schools, families, and communities in implementing habit-based character education